Evidence for an Interaction Between Age at 1(st) Drink and Genetic Influences on DSM-IV Alcohol Dependence Symptoms - Agrawal, Arpana (2009)
BACKGROUND: Research suggests that individuals who start drinking at an early age are more likely to subsequently develop alcohol dependence. Twin studies have demonstrated that the liability to age at 1(st) drink and to alcohol dependence are influenced by common genetic and environmental factors, however, age at 1(st) drink may also environmentally mediate increased risk for alcohol dependence. In this study, we examine whether age at 1(st) drink moderates genetic and environmental influences, via gene x environment interactions, on DSM-IV alcohol dependence symptoms. METHODS: Using data on 6,257 adult monozygotic and dizygotic male and female twins from Australia, we examined the extent to which age at 1(st) drink (a) increased mean alcohol dependence symptoms and (b) whether the magnitude of additive genetic, shared and non-shared environmental influences on alcohol dependence symptoms varied as a function of increasing age at 1(st) drink. Twin models were fitted in Mx. RESULTS: Risk for alcohol dependence symptoms increased with decreasing age at 1(st) drink. Heritable influences on alcohol dependence symptoms were considerably larger in those who reported an age at 1(st) drink prior to 13 years of age. In those with later onset of alcohol use, variance in alcohol dependence was largely attributable to non-shared environmental variance (and measurement error). This evidence for unmeasured gene x measured environment interaction persisted even when controlling for the genetic influences that overlapped between age at 1(st) drink and alcohol dependence symptoms. CONCLUSIONS: Early age at 1(st) drink may facilitate the expression of genes associated with vulnerability to alcohol dependence symptoms. This is important to consider, not only from a public health standpoint, but also in future genomic studies of alcohol dependence.